Psychotherapy and brain plasticity - Collerton, Daniel (Frontiers in Psychology, 2013)
In this paper, I will review why psychotherapy is relevant to the question of how consciousness relates to brain plasticity. A great deal of the research and theorizing on consciousness and the brain, including my own on hallucinations for example (Collerton and Perry, 2011) has focused upon specific changes in conscious content which can be related to temporal changes in restricted brain systems. I will argue that psychotherapy, in contrast, allows only a focus on holistic aspects of consciousness; an emphasis which may usefully complement what can be learnt from more specific methodologies.